1992
DOI: 10.3109/00048679209072095
|View full text |Cite
|
Sign up to set email alerts
|

Suicide in Singapore, 1986

Abstract: Three hundred and forty-two cases of suicide in Singapore (1986) were studied. The rates were highest among Indians males. Jumping from a height was the method used by 60% of the subjects, and the predominant associated factor as ascertained by the coroner was illness (51%), both physical and mental. About 40% had seen a doctor in the year prior to their death, and 20% had a history of a previous suicide attempt. The majority of cases killed themselves during the daylight hours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
4
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 23 publications
3
4
0
Order By: Relevance
“…In our study there was almost uniform diurnal variation with a slight increase in day light occurrence (52%), which has also been observed in other regional countries like Singapore. 3 Financial burden (37%) followed by marital disharmony (35%) are the two most common causes of suicide and is similar to previous findings. 1 Quite contrast to our findings, studies in South Carolina, USA 4 and in Japan 14 suggest dreadful diseases followed by problems of economic distress to be the two most common causes of suicide.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In our study there was almost uniform diurnal variation with a slight increase in day light occurrence (52%), which has also been observed in other regional countries like Singapore. 3 Financial burden (37%) followed by marital disharmony (35%) are the two most common causes of suicide and is similar to previous findings. 1 Quite contrast to our findings, studies in South Carolina, USA 4 and in Japan 14 suggest dreadful diseases followed by problems of economic distress to be the two most common causes of suicide.…”
Section: Discussionsupporting
confidence: 89%
“…This observation was identical with the available literatures. 2,3,5,12 This is expected, as this age group comprises the majority of the population. But a study in Japan, 14 Mexico 7 and in South Carolina, USA, 4 revealed the age group of over 65 years was common, which were the least sufferers in our study.…”
Section: Discussionmentioning
confidence: 88%
“…Cities by nature have a high population density with more easily accessible multistory buildings. Our finding is consistent with other studies demonstrating a higher number of suicides in metropolitan areas (Fischer et al, 1993; Marzuk et al, 1992; Peng & Choo, 1992). Although it may be expected that more bridges are found in urban areas, suicide by jumping from bridges did not significantly correlate with population density.…”
Section: Discussionsupporting
confidence: 94%
“…The numbers of suicides by jumping show marked regional differences, mostly dependent on accessibility of structures to jump from (Ross & Lester, 1991). High numbers of suicides by jumping have been reported from Brussels, Belgium, (Moens, Loysch, & van de Voorde, 1988); New York, USA (Fischer, Comstock, Monk, & Sencer, 1993); Singapore (Peng & Choo, 1992); and Bern, Switzerland (Reisch & Michel, 2005). The phenomenon is explained in part by the fact that persons who kill themselves by jumping tend to go to sites close to their place of residence (Ross & Lester, 1991; Wohner & Schmidtke, 2005).…”
mentioning
confidence: 99%
“…Suicide by jumping from high places is a method typically used when such places are easily accessible, like in Singapore or New York, where 60% (Peng & Choo, 1992; Ung, 2003) or, respectively, 30% (Fischer, Comstock, Monk, & Sencer, 1993) commit suicide with this method. Even in small countries like Belgium the percentage of jumping compared to all methods varies by region (Moens, Loysch, & van de Voorde, 1988), implying that the use of methods depends on local availability (Hawton, Fagg, Simkin, Harriss, & Malmberg, 1998).…”
mentioning
confidence: 99%